Stochastic forecast of the population of Central Serbia based on empiric forecast errors - Nikitović Vladimir (Stanovništvo, 2007)
Based on the example of the forecast of the population of Central Serbia for the 2005-2032 period, the basic probabilistic concept in forecasting the trends of demographic components of population development have been presented. The stochastic element of forecast is based on the analysis of empirical forecast errors of corresponding indicators of demographic development. The analysis frameworks were forecasts of official bureaus of statistics published during the second half of the 20th century. The statistical distribution of probability for chosen forecast parameters were formed around so called middle variant of corresponding indicators in the current national forecast of population, published by the Statistical Office of the Republic of Serbia (SORS) for the period 2002-2032. The basic characteristics of the probabilistic approach of forecasting were presented through mutual comparison of the main methodological assumptions, namely though comparative demographic-statistical valorization of results with traditional deterministic concept, represented by forecasts of RSB. The stochastic forecast of the population of Serbia clearly indicated to the key advantages of this approach: methodological consistency in quantifying demographic indicators as well as the possibility of transparent usage of results in numerous aspects of social planning. In this way the significance of the necessity for the elaboration of a studious national forecast of the population of Serbia completely based on a stochastic basis has been stressed, regardless of the still-present restrictions in the development of the probabilistic approach.